Absolute Fear - Jackson, Lisa (Rutherford, NJ : Kensington Pub., 2007)
From the New York Times bestselling author of Fatal Burn and Shiver comes a pulse-pounding new novel of madness, deceit, and twisted revenge that will take readers into the heart of fear.
Keywords: Serial murders; New Orleans (La.); Suspense fiction